Pakistan in China’s Security Policy in the Context of the US Indo-Pacific Strategy (Economic and Political Thought, 2023)
The aim of the article is to analyze the importance of Pakistan, as one of theinfluential countries of the Indo-Pacific region, for the broadly understoodsecurity of China during the rule of Xi Jinping in the context of the Americanstrategy in the region. Pakistan is undoubtedly one of the participantsin the competition between the US and China. Its geographical locationis of geostrategic and geoeconomic importance for Beijing. Pakistan playsan important role in the process of redefining China’s security interests in theIndo-Pacific region and increases its power projection capabilities. Beijing’srelations with Islamabad are filled with new content, especially in the contextof formulating the American concept of regional security, which has a clearlyanti-Chinese character. The US system of alliance ties in the Indo-Pacificregion is based on countries whose relations with China are tense and historicallyburdened. India ranks first among these countries. In this context,Pakistan serves as an ally to China that expands its room for maneuver in theprocess of balancing relations in the region.
Keywords: China, Pakistan, US, Indo-Pacific, CPEC, Belt and Road Initiative (BRI)